Post-Trauma Communication Behavior of Incest Victims in Bengkulu: A Qualitative Study Using the Spiral of Silence Framework - Poppi Damayanti; Triyani Pujiastuti; Rahmat Taufiq Hidayat; Rohmadina (INJECT (Interdisciplinary Journal of Communication), 2026)
Handling and prevention of incest cases in Bengkulu Province to date. This is still done in a partial and limited way, based on limited data, so that interventions provided have not yet addressed the root problem comprehensively. The absence of complete profiles of victims and perpetrators causes service mentoring to be sectoral in nature, for example, only focusing on economic aspects, without considering the psychosocial and communication factors in the family. Research This aim is to describe the incest victim profile in a demographic way, as well as analyze the behavior, communication, and patterns of victim communication, both intrapersonal, interpersonal, and family communication, as a basis for better prevention and recovery strategies. Research uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, discussion groups, focused group discussions (FGD), and study documentation. The informant was determined by purposive sampling. Data analysis was carried out using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and withdrawal conclusion. Research results show that all victims of incest are women of various sexes, ranging in age from 6 to 15 years, originating from families that were pre-prosperous and experiencing family disintegration. Perpetrator is a member of the nuclear family and relatives close to the age of 26–54 years. Victims face social stigma, bullying, and discrimination post-event. Psychologically, the victim experiences deep trauma, anxiety, withdrawal, self-Concept, and negative Concept. From the aspect of communication, found disturbance in intrapersonal communication, barriers in interpersonal communication, as well as patterns of communication in closed and dysfunctional families. Findings. This confirms that incest is a complex phenomenon that requires an intervention-based approach to victim profiles and improved patterns of communication within families in a holistic way.